Reversible Watermarking Algorithm with Distortion Compensation. (10th January 2011) - Sachnev Sachnev, Vasiliy Vasiliy; Kim Kim, Hyoung Joong Hyoung Joong; Suresh Suresh, Sundaram Sundaram; Shi Shi, Yun Qing Yun Qing
Abstract : A novel reversible watermarking algorithm with two-stage data hiding strategy is presented in this paper. The core idea is two-stage data hiding (i.e., hiding data twice in a pixel of a cell), where the distortion after the first stage of embedding can be rarely removed, mostly reduced, or hardly increased after the second stage. Note that even the increased distortion is smaller compared to that of other methods under the same conditions. For this purpose, we compute lower and upper bounds from ordered neighboring pixels. In the first stage, the difference value between a pixel and its corresponding lower bound is used to hide one bit. The distortion can be removed, reduced, or increased by hiding another bit of data by using a difference value between the upper bound and the modified pixel. For the purpose of controlling capacity and reducing distortion, we determine appropriate threshold values. Finally, we present an algorithm to handle overflow/underflow problems designed specifically for two-stage embedding. Experimental study is carried out using several images, and the results are compared with well-known methods in the literature. The results clearly highlight that the proposed algorithm can hide more data with less distortion.